Robust measurement of clinical improvement in patients with cutaneous lupus erythematosus - Benjamin A Nanes; Jane L Zhu; Benjamin F Chong (Lupus Science and Medicine)
Objective The severity and disease course of cutaneous lupus erythematosus (CLE) are highly variable. Consequently, outcome measures for CLE clinical improvement are heterogeneous, complicating treatment decisions and therapeutic development. This study characterises CLE outcome measures and identifies the influence of clinical improvement thresholds on strengths of associations with patient demographic and clinical factors.Methods In this pilot cohort study, multivariable models identified factors associated with CLE activity and skin damage improvement, defined as relative decreases in Cutaneous Lupus Activity and Severity Index (CLASI) activity (CLASI-A) and damage (CLASI-D) scores, over ranges of response thresholds.Results 66 patients with 119 visit-pairs were included in the CLASI-A analysis. 74 patients with 177 visit-pairs were included in the CLASI-D analysis. Factors associated with CLE activity and damage improvement depended on the response threshold. Some associations were stronger at more stringent thresholds, including subacute CLE predominance with increased likelihood of CLASI-A improvement (R2=0.73; 50% reduction: OR 1.724 (95% CI 0.537 to 5.536); 75%: 5.67 (95% CI 1.56 to 20.5)) and African-American race with decreased likelihood of CLASI-D improvement (R2=0.80; 20%: 0.40 (95% CI 0.17 to 0.93); 40%: 0.25 (95% CI 0.08 to 0.82)). Other associations were stable across multiple thresholds, including older age of CLE development with increased likelihood of CLASI-A improvement (R2=0.25; 50%: 1.05 (95% CI 1.01 to 1.09]; 75%: 1.05 (95% CI 1.00 to 1.10)) and higher initial disease activity with decreased likelihood of CLASI-D improvement (R2=0.55; 20%: 0.91 (95% CI 0.84 to 0.98); 40%: 0.88 (95% CI 0.79 to 0.97)).Conclusions Examining a range of CLASI threshold outcomes can comprehensively characterise changes in disease course in patients with CLE. Insufficiently stringent thresholds may fail to distinguish meaningful clinical change from natural fluctuation in disease activity.